Historical Milestone of the Ukrainian Revolution - Baran, Volodymyr (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
Review on the publication: Western Ukrainian People's Republic 1918-1923. Encyclopaedia Vol. 1: A-Ж. Ivano-Frankivsk : Manuscript-Lviv, 2018. 688 p.; West Ukrainian People's Republic 1918-1923. Encyclopaedia Vol. 2: З-O. Ivano-Frankivsk : Manuscript-Lviv, 2019. 832 p.; West Ukrainian People's Republic 1918-1923. Encyclopaedia Vol. 3: P-С. Ivano-Frankivsk : Manuscript-Lviv, 2020. 576 p.; West-Ukrainian People's Republic 1918-1923. Encyclopaedia Vol. 4: T-Я. Ivano-Frankivsk : Manuscript-Lviv, 2021. 688 p. (Head of the Editorial Board I. Tsependa, Head of the Editorial Board M. Kuhutiak).